ANALISIS YURIDIS GUGATAN ACTIO PAULIANA SEBAGAI BENTUK PERLINDUNGAN TERHADAP KREDITUR DALAM UNDANG-UNDANG NOMOR 37 TAHUN 2004 TENTANG KEPAILITAN DAN PKPU (Study Kasus Putusan Nomor 018PK/Pdt.Sus/2007) - Aida Nur Hasanah; Sunarmi Sunarmi; Mahmul Siregar; Dedi Harianto (Universitas Sumatera Utara, 2018)
ABSTRACT Actio Pauliana granted as a protection to creditors for debtors that inflict a financial loss. Actio Pauliana is regulated on article 41 to article 50 of insolvency constitutional and PKPU. The real practice of Actio Pauliana took case on the submission of the head of Association House of Legacy Semarang as the curator. Based on verdict no. 02/PAILIT/2006/PN.Niaga.Smg jo 017K/N/2007 jo 018PK/Pdt.Sus/2007, The Panel of Judges repudiate the judicial review of BHP. The Panel of Judges Propositions was neither the evidence could prove the debtor’s bankruptcy nor the thrid party ascertains that the sales and purchases agreement will cause a financial loss for the creditors. However, the transactions between debtors and the thrid party effects on the diminished of the bankrupt assets, that leads to a financial loss for the creditor. This research is conducted to find out that Actio Pauliana could give law protection from curator to creditor, the circumscription of well-doing an unwell-doing debtors on their bankrutcy assets transfer, and the application of Actio Pauliana law by the Panel Judges according to verdict number 018PK/Pdt.Sus/2007. The result showed that Actio Pauliana legal action number: 018 PK/Pdt.Sus/2007 hasn’t granted protection to creditors. The repudiate verdict from panel judges cause an improbability of annulment of insolvency debtors and thrid parties law action, thus the insolvency assets stand still on the thrid party side and reduce the book price of the assets. This Panel Judge’s repudiate verdict as a final judgment was taken because of lack of evidence from the curator. Meanwhile based on the fact of the case, insolvency assets sales and purchases agreement should be held within 1 year before the insolvency proceedings being announced, and this action is not compulsory for the debtors. Insolvency assets sales and purchases agreement agreed upon debtors and third parties are for lawer than the market price, affecting the diminished of insolvency assets that continuously cause a financial loss for another insolvency creditors. The absence of good will specification on the insolvency constitution. Insolvency constitutional and PKPU, is determined to be the cause of different perspective for the judges to finalize the judgement of Actio Pauliana submission. Keywords : Insolvency, Actio Pauliana, Creditors